Apache Ignite Quick Start Guide : Distributed Data Caching and Processing Made Easy. - Acharya, Sujoy (Packt Publishing Ltd, 2018)
Apache Ignite is a distributed in-memory platform designed to scale and process large volume of data. It can be integrated with microservices as well as monolithic systems, and can be used as a scalable, highly available and performant deployment platform for microservices. This book will teach you to use Apache Ignite for building a high ...